Plant Associated Rhizobacteria for Biocontrol and Plant Growth Enhancement - Jiao, Xiurong; Takishita, Yoko; Zhou, Guisheng; Smith, Donald L. (Frontiers in Plant Science, 2021)
Crop disease remains a major problem to global food production. Excess use of pesticides through chemical disease control measures is a serious problem for sustainable agriculture as we struggle for higher crop productivity. The use of plant growth promoting rhizobacteria (PGPR) is a proven environmentally friendly way of controlling plant disease and increasing crop yield. PGPR suppress diseases by directly synthesizing pathogen-antagonizing compounds, as well as by triggering plant immune responses. It is possible to identify and develop PGPR that both suppress plant disease and more directly stimulate plant growth, bringing dual benefit. A number of PGPR have been registered for commercial use under greenhouse and field conditions and a large number of strains have been identified and proved as effective BCAs under environmentally controlled conditions. However, there are still a number of challenges before registration, large-scale application, and adoption of PGPR for the pest and disease management. Successful BCAs provide strong theoretical and practical support for application of PGPR in greenhouse production, which ensures the feasibility and efficacy of PGPR for commercial horticulture production. This could be pave the way for widespread use of BCAs in agriculture, including under field conditions, to assist with both disease management and climate change conditions.